Perceived Stress in Adults Aged 65 to 90: Relations to Facets of Time Perspective and COMT Val158Met Polymorphism - Rönnlund, Michael; Åström, Elisabeth; Adolfsson, Rolf; Carelli, Maria G. (Frontiers in Psychology, 2018)
This study examined the relation between perceived stress and time perspective (views of past, present, future) in a population-based sample of older adults (65-90 years, N = 340). The Perceived Questionnaire (PSQ index) was used to measure stress and the Swedish version of the Zimbardo Time Perspective Inventory (S-ZTPI) was used to operationalize time perspective. Unlike the original inventory, S-ZTPI separates positive and negative aspects of a future time perspective and we hypothesized that the Future Negative scale would be important to account for variations in stress. Additionally, associations with Catechol-O-methyltransferase (COMT) Val158Met polymorphism were examined, motivated by prior associations of this single nucleotide polymorphism (SNP) with stress (or “anxiety”) related personality traits. In line with the hypotheses, Future Negative was the strongest predictor of PSQ index scores in multiple regression analyses. In related vein, the dichotomization of the unitary Future scale increased the association between PSQ scores and a measure of deviations from a balanced time perspective, i.e. a difference between proposed optimal and observed ZTPI profile. Finally, higher levels of stress as well as higher scores on Future Negative were observed in COMT Val/Val carriers, at least among men. This suggests a shared dopaminergic genetic influence on these variables. Collectively, the results demonstrate that perceived stress is closely linked to time perspective and highlight the need to take negative aspects of a future temporal orientation into account to understand this relation.